Migração para computação distribuída em Business Intelligence - Filipa Ivars de Sousa e Silva (2018)
E-commerce is an emerging business and, with its growth, it also increases the volume of stored data. Farfetch is a technological innovator company in the same area that operates in the international market and already has a large audience. It sells on its online channel fashion articles from the most renowned fashion boutiques and accessories scattered around the world. Along with the growth of the company, there are limitations in data storage and difficulties in making and maintaining a system that allows autonomy in the consultation of this information by professionals who perform tasks of analysis and interpretation of data. At the same time, it is necessary to look for answers to these problems based on currently available solutions that can efficiently manage this large volume of data and apply business intelligence and data-warehousing principles to its organization and interpretation. Farfetch has implemented a response to these problems, and in this document, we intend to study these solutions, compare them to the already implemented solution, to understand which, or which ones, to be the most appropriate and how their transition should be done. It is sought that the response obtained increases the capacity and scalability of the storage of a large amount of data, increase the efficiency and reduce the response time of the requests to the data-warehouse, foresee a greater autonomy of other professionals, such as managers and analysts in the information query, and finally, it is intended to predict / analyze its long-term performance.